DISTRIBUCIÓN FUNCIONAL DEL INGRESO Y RÉGIMEN DE CRECIMIENTO EN MÉXICO Y ESPAÑA - JOSE RAUL LUYANDO CUEVAS; JULIO HERRERA REVUELTA (Cuadernos de Economía, 2018)
The purpose of neoliberal reforms was to stimulate private investment and exports, and, therefore, generate higher growth and employment. However, these changes have generated a significant drop in the share of wages in income in both developed and developing countries since the late 70s. This study was undertaken using post-Keynesian theory; however, it made changes to investment and exportation functions so that the functional distribution has a greater weight in the estimations. We found that the wage moderation policies have adversely influenced the inner components of demand; while Spain is wage-led, Mexico is profit-led.